Potencial turístico de agroindústrias familiares como opção de desenvolvimento rural sustentável no município de Guaraniaçu/PR - Salvadori , Sergio Luiz (2019)
This paper aims to evaluate the family agroindustry's touristic potential as an option for sustainable rural development in the Guaraniaçu city, on Paraná. To do so, we searched 24 properties that have agribusinesses associated with family farming activity in that city. At the same time, we have reviewed papers published less than 10 years about this topic on journal websites, which pointing to the fact that associating rural tourism with food production is a viable and important alternative or additional income to family farmers working in agro-industry. To implement this project, we conducted an inventory with diagnosis, prognosis, assessment of agroindustries' tourism potential and a survey on 24 properties of the city during June 2018, whose data were analyzed by “FOFA Matrix”. It is possible to affirm that the strengths found in the properties analyzed were access, food products of the agroindustries that attract the consumer and the region natural characteristics; On the other hand, the weaknesses are the lack of skilled labor and properties infrastructure. Regarding the opportunities, we observed the proximity to the cities of Cascavel, Laranjeiras do Sul and Quedas do Iguaçu and among the threats, the lack in the tourism activities involvement , the low number of people in the properties, the lack local labor supply and a low number of descendants to continue the enterprises. We conclude that the introduction of rural tourism activities in family farming is viable because it complements the family’s income and by improving the activities quality and the quality of life in the Guaraniaçu city.